The association of body roundness index and body mass index with frailty and all-cause mortality: a study from the population aged 40 and above in the United States - Jianqiang Zhang; Huifeng Zhang (Lipids in Health and Disease)
Abstract Background The relationship between body roundness index (BRI), a new obesity index, and frailty has not been established. This study aims to compare the associations of traditional obesity index body mass index (BMI) and BRI with frailty and the risk of all-cause mortality. Methods The clinical data of 15,157 participants over 40 years old from the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2018 were analyzed. Based on weighted logistic regression, COX regression and restricted cubic spline, the associations of BRI and BMI with the odds of frailty and the risk of all-cause mortality were estimated. The receiver operating characteristic curve (ROC) and concordance index were used to evaluate the ability of BRI and BMI to predict frailty and survival. Results Weighted logistic regression showed that the odds of frailty showed a trend of increasing with the increase of BRI and BMI (P for trend < 0.0001, respectively). After adjusting for all confounding factors, the association between BRI and frailty was stronger (OR: 1.20, 95% CI: 1.13–1.27, P < 0.0001), and the association between BMI and frailty was slightly weaker (OR: 1.14, 95% CI: 1.08–1.21, P < 0.0001). ROC showed that the area under the curve (AUC) of BRI for predicting frailty was 0.628, while the AUC of BMI was 0.603, and the difference between the two was significant (PDeLong < 0.001). In addition, in survival analysis, BRI and BMI showed a significant U-shaped association with the risk of all-cause mortality. Piecewise regression based on the inflection point shows that when BRI < 7.33, an increase in BRI reduces the risk of all-cause mortality (HR: 0.85, 95% CI: 0.78–0.92, P < 0.0001), while when BRI ≥ 7.33, an increase in BRI increases the risk of all-cause mortality (HR: 1.19, 95% CI: 1.03–1.38, P = 0.02); when BMI < 33.57, an increase in BMI reduces the risk of all-cause mortality (HR: 0.84, 95% CI: 0.78–0.91, P < 0.0001), and when BMI ≥ 33.57, an increase in BRI increases the risk of all-cause mortality (HR: 1.18, 95% CI: 1.04–1.34, P = 0.01). Moreover, the time-dependent c-index curve showed that the ability of BRI to predict the risk of all-cause mortality in frail people was comparable to that of BMI. Conclusion In the American population over 40 years old, both BRI and BMI are independently and positively associated with frailty. Moreover, BRI has a stronger ability to predict frailty than BMI. In addition, both BRI and BMI have a U-shaped association with the risk of all-cause mortality in frail individuals, and the two have comparable abilities to predict the risk of all-cause mortality.